2016
DOI: 10.3389/fmicb.2016.01846
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Antibiotic Resistance Genes in Coagulase-Positive-and Negative-Staphylococcus in Chicken Meat Retailed to Consumers

Abstract: The use of antibiotics in farm management (growing crops and raising animals) has become a major area of concern. Its implications is the consequent emergence of antibiotic resistant bacteria (ARB) and accordingly their access into the human food chain with passage of antibiotic resistance genes (ARG) to the normal human intestinal microbiota and hence to other pathogenic bacteria causative human disease. Therefore, we pursued in this study to unravel the frequency and the quinolone resistance determining regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 89 publications
9
50
1
2
Order By: Relevance
“…Similar to our findings, high distribution of mecA, gyrA, grlA and cfr was also described in the S. aureus bacteria recovered from chicken meat in Egypt. 46 Another Iranian investigation 47 showed that oxacillin, gentamicin, penicillin, tetracycline and erythromycin resistant S. aureus bacteria recovered from milk and dairy products carried considerable incidence of blaZ, aacA-aphD, mecA, tetK and tetM, ermB, ermA, ermT, ermC, msrB and msrA antibiotic resistance markers likewise to our survey.…”
Section: Discussionsupporting
confidence: 76%
“…Similar to our findings, high distribution of mecA, gyrA, grlA and cfr was also described in the S. aureus bacteria recovered from chicken meat in Egypt. 46 Another Iranian investigation 47 showed that oxacillin, gentamicin, penicillin, tetracycline and erythromycin resistant S. aureus bacteria recovered from milk and dairy products carried considerable incidence of blaZ, aacA-aphD, mecA, tetK and tetM, ermB, ermA, ermT, ermC, msrB and msrA antibiotic resistance markers likewise to our survey.…”
Section: Discussionsupporting
confidence: 76%
“…While Aslantaş et al [51] investigated that 89 isolates of (CNS) susceptible to Tetracycline (100%). Osman et al [52] reported that 36 CNS isolates recovered from chicken meat showed complete resistance to Sulfamethoxazole/Trimethoprim. Aslantaş et al [51] investigated 69.2% out of 89 isolates CNS were resistant while 2.6% of S. scuiri, S. lentus, and S. epidermidis were resistant by Huber et al [11].…”
Section: Resultsmentioning
confidence: 99%
“…Aslantaş et al [51] investigated 69.2% out of 89 isolates CNS were resistant while 2.6% of S. scuiri, S. lentus, and S. epidermidis were resistant by Huber et al [11]. Resistance to Clindamycin was reported [52,53]. Complete resistance to Oxacillin was also reported [14,18,52] while Piessens et al [54] found 42.9% resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings were noted in Iranian hospital food workers who reported that all the Staphylococcus strains resist to penicillins (100%) and showed high resistance rates to ofloxacin (88%), tobramycin (73·90%), ciprofloxacin (70%) and cefoxitin (50%) (Safarpoor Dehkordi et al ), while in China O'Donoghue et al noted a very low percentage of resistance against Penicillin GG among food workers (1·1%) (Ho et al ). In general, the highest rates of resistance associated to nasal carriage worldwide are reported among the food handlers exposed to livestock or raw meats (Hoet et al ; Osman et al ; Fetsch ; Parisi et al ; Wu et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Letters in Applied Microbiology 70, 241--251 © 2020 The Society for Applied Microbiology It is the reason for a big distress in both human and veterinary medicines specially with the increasing tendency of Staphylococcus sp. to develop antibiotic resistance (WHO 2014;Osman et al 2016). Moreover, coagulasenegative Staphylococcus (CoNs) which were considered as innocuous skin commensal bacteria prior 1970s, gained importance and are classified as important causes of human infections (Osman et al 2016).…”
Section: Introductionmentioning
confidence: 99%